A Case Report On Peripartum Cardiomyopathy - Safder, AMB; Mir, SA; Miah, BM; Tamanna, RJ; Mohibullah, AKM (BIRDEM Medical Journal, 2012)
A 32 year-old primigravida with gestational diabetes & subclinical hypothyroidism on replacement therapy and no previous cardiac problem, developed features of shock few hours after elective caesarian section at term, in the absence of any chest pain or palpitation. Following resuscitation she developed features of acute left ventricular failure. ECG showed nonspecific T changes, chest x-ray revealed enlarged cardiac shadow with pulmonary congestion, arterial blood gas analysis was normal with supplemental oxygen. Serial cardiac markers were normal & serum d-Dimer was negative. Echocardiogram revealed dilatation of all cardiac chambers with global hypokinesia & severe left ventricular (LV) systolic dysfunction. She was diagnosed as a case of peripartum cardiomyopathy and treated conservatively with medications. Her condition improved dramatically & she became symptom-free by the 5th post-operative day (POD) and subsequently discharged on 9th POD. Follow-up echocardiogram after 6 weeks revealed regional wall motion abnormality, normal chamber dimensions and fair LV systolic function. DOI: http://dx.doi.org/10.3329/birdem.v1i1.12387 Birdem Med J 2011; 1(1): 37-42